Prospek Sistem Resi Gudang Untuk Meningkatkan Daya Saing Komoditas Lada - R Ferry Bakti Atmaja; Seno Hadi Saputro (Universitas Bina Sarana Informatika, 2020)
It has become the hope for the people and the government of Bangka to re-cherish pepper commodities as before, the Warehouse Receipt System program is one of the efforts expected to fulfill that dream. This research is a qualitative study that seeks to answer the question of the ability of the prospect of the Warehouse Receipt System program in increasing the competitiveness of pepper commodities. Primary data collection techniques using interviews and questionnaires to pepper farmers located in Mendo Barat District, Bangka Regency. The results of the study stated that the WRS program has not been able to contribute to increasing the competitiveness of pepper commodities in terms of the functioning of the maximum market mechanism, maintained integrity of environmental carrying capacity for quality commodities / agricultural products, the establishment of legal certainty, and a competitive business world